2021
DOI: 10.1177/20458940211012366
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic significance of pleural effusions in pulmonary arterial hypertension

Abstract: It has been suggested pleural effusions may develop in right heart failure in the absence of left heart disease. The incidence and prognostic significance of pleural effusions in pulmonary arterial hypertension (PAH) is uncertain. Patients with PAH followed at our tertiary care center were reviewed. Survival was examined based on the subsequent development of a pleural effusion. 191 patients with PAH met the inclusion criteria. The prevalence of pleural effusions on initial assessment was 7.3%. Among patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This lends further support to the hypothesis that right ventricular–pulmonary artery uncoupling and resulting elevation of central venous pressure may impede lymphatic flow and lead to pulmonary oedema and increased B‐lines. This is very similar to the pathophysiology hypothesized in the development of pleural and pericardial effusions in isolated PAH 14 …”
Section: Figuresupporting
confidence: 83%
“…This lends further support to the hypothesis that right ventricular–pulmonary artery uncoupling and resulting elevation of central venous pressure may impede lymphatic flow and lead to pulmonary oedema and increased B‐lines. This is very similar to the pathophysiology hypothesized in the development of pleural and pericardial effusions in isolated PAH 14 …”
Section: Figuresupporting
confidence: 83%
“…During the occurrence and development of TR, TR is often accompanied by an increase in pulmonary artery pressure and atrial pressure, which is the cause of pericardial effusion. There is no significant difference in the volume of pericardial effusion between patients with isolated pulmonary venous hypertension or systemic hypertension, but in the presence of both, the volume of pericardial effusion increased due to obstruction of pericardial venous return due to elevated right atrial pressure [25,26]. In this study, we found an association between pericardial effusion and moderate-to-severe tricuspid regurgitation, but further associations between them require further validation in relevant studies.…”
Section: Tricuspid Regurgitation Is Very Common In Patients Undergoin...mentioning
confidence: 50%
“…In our study, the mPAP in IPAH group was significantly lower than that in PAH-CHD group, but a higher baseline PVR implied more severe pulmonary vascular disorders in the IPAH cohort. Pericardial effusion, a relatively common complication of PAH, is associated with increased mortality ( Fenstad et al, 2013 ; Shimony et al, 2013 ; Chandel et al, 2021 ). In this study, the incidence of pericardial effusion (40.5%) in patients with IPAH was similar to that in Shimony’s study (47.1%), which may be related to RV dysfunction and subsequent increased right atrial filling pressure ( Shimony et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%